The Ritual Culture of Victorian Professionals : Competing for Ceremonial Status, 1838-1877. - Pionke, Albert D. (Taylor and Francis, 2016)
Focusing on the middle decades of the nineteenth century, Pionke's book historicizes the relationship of ritual, class and public status in Victorian England. Through analysis of magazines, court cases, law books, manuals and works by authors that include William Makepeace Thackeray, Thomas Hughes, Anthony Trollope, Charles Dickens, George Eliot and Elizabeth Barrett Browning, Pionke's book excavates Victorian professionals' vital ritual culture and writers' place in the zero-sum contest for professional status.